PENGARUH PROFITABILITAS DAN CAPITAL INTENSITY TERHADAP TAX AVOIDANCE: Kompetensi Dewan Komisaris Sebagai Variabel Pemoderasi - Yoseph Togu Marsahala, (2020)
This study aims to discuss and study the profitability and capital intensity of tax avoidance with the competence of the board of commissioners as a moderating variable. The independent variable in this study is profitability and capital intensity. The population in this study was 166 manufacturing companies listed on Indonesia Stock Exchange in 2016-2018. The sample used in the study amount to 291 samples obtained from 97 manufacturing companies. This study uses data analysis techniques namely panel data regression analysis using the STATA version 13 application with a significance level of 5%. The results of this study indicate that profitability has a significant effect on tax avoidance and capital intensity is not significant on tax avoidance. The competence of the board of commissioners has a significant effect on the effect of profitability on tax avoidance and the competency of commissioners has no significant effect on the effect of capital intensity on tax avoidance.